Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler

Variation in Antarctic Petrel Foraging Ecology: Not All Individuals Specialize on Krill - Descamps, Sébastien; Harris, Stephanie; Fluhr, Julie; Bustamante, Paco; Cherel, Yves; Trevail, Alice; Brault-Favrou, Maud; Patrick, Samantha (Frontiers in Marine Science, 2022)
Individual heterogeneity in foraging behaviour determines how individuals and populations respond to changes in the availability and distribution of resources. Antarctic krill Euphausia superba is a pivotal species in Southern Ocean food webs and an important target for Southern Ocean fisheries. Changes in its abundance could dramatically impact marine predators, with effects depending on the extent to which all individuals rely on krill as prey. The Antarctic petrel Thalassoica antarctica is a high latitude seabird thought to be dependent on krill in part of its breeding range. Here, by combining fine-scale GPS tracking of petrel foraging trips with diet data, we examined the level and consistency of inter-individual variation in foraging strategies in breeding Antarctic petrels in Dronning Maud Land, Antarctica, and assessed whether all individuals share a similar reliance on Antarctic krill. We found that Antarctic petrels showed high levels of repeatability in their diet and foraging movements at sea, indicating consistent individual differences in foraging strategies. During consecutive foraging trips, petrels tend to make trips of similar lengths and durations to reach similar terminal locations and to feed on similar prey. These individual differences in diet were spatially structured, with individuals travelling towards the west consuming a more fish-based diet. These different foraging tactics did not appear to be associated with different costs and/or benefits as adult body mass, chick survival and chick growth were unrelated to birds’ foraging movements and diet. Our results show that, even if a large part of the population may be dependent on krill, some individuals specialize on fish. Such inter-individual variation in foraging suggests that this population could be more resilient to changes in the marine environment, such as a decline in krill abundance or a shift in krill distributions.
Keywords: Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler; zoologi

På jobb - lang borte fra kontoret - blant spektakulære fjell og landskap - Elvevold, Synnøve (Polarboken, 2022)
Keywords: Dronning Maud Land; geologi

Cavernous Decay of Granite and Granitic Gneiss, Central Dronning Maud Land, Antarctica - Engvik, Ane K; Elvevold, Synnøve; Myhre, Per Inge (The Journal of Geology, 2022)
Tafoni are a type of cavernous weathering that is found in a variety of rock types and locations around the world. Tafoni have been documented in a number of climatic zones ranging from hot and cold deserts to moist coastal environments. Despite the widespread distribution of tafoni, the major processes controlling tafoni weathering are not well understood and are still a matter of discussion. This study addresses the frequent distribution of well-developed tafoni in the cold, arid environment of the inland mountain range of central Dronning Maud Land, Antarctica. The aim is to document and characterize the nature of tafoni present in Gjelsvikfjella (2°E) eastward to Filchnerfjella (8°E) and to discuss formation processes. The cavities occur in groups and are typically spherical to oval shaped. They range in diameter and depth from 1 dm up to 1.5 m. The cold, arid environment of this region favors mechanical weathering mechanisms such as freeze-thaw actions and wind abrasion. Furthermore, the structural, textural, and mineralogical properties of the parent rock can potentially have a strong control on weathering and cavity development. Observed tafoni are typically formed in massive granitoid intrusives and granitic gneisses and migmatites. Chemical dissolution of pyroxene to iddingsite and radiation from rare earth element–bearing accessory minerals cause microfracturing, which facilitates freeze-thaw actions and accordingly enhances the weathering.
Keywords: Dronning Maud Land; geologi

Synthesis of field and satellite data to elucidate recent mass balance of five ice rises in Dronning Maud Land, Antarctica - Goel, Vikram; Morris, Ashley; Moholdt, Geir; Matsuoka, Kenichi (Frontiers in Earth Science, 2022)
We investigated mass balance changes over five ice rises in the last few decades near Fimbul and Nivl ice shelves in central Dronning Maud Land. We use the Input-Output Method constrained using field-based geophysical measurements conducted during the austral summers of 2012–14 over three ice rises near the Fimbul Ice Shelf. Further, we use satellite altimetry data (ICESat, ICESat-2, and CryoSat-2) to estimate geodetic mass balance over all five ice rises in recent decades. Both field- and satellite-based estimates show that until 2010, three out of five ice rises were thickening (0.4–0.2 mieq a−1) while two were close to balance. However, over the last decade, the ice rises thickening previously started to thin (−0.2–−0.6 mieq a−1) while the other two remained close to balance. Much of this variability is likely associated with regional surface mass balance trends, with each ice rise exhibiting its characteristics depending on its local glaciological settings.
Keywords: Dronning Maud Land; geofysikk; glasiologi

A review of the scientific knowledge of the seascape off Dronning Maud Land, Antarctica - Lowther, Andrew; von Quillfeldt, Cecilie; Assmy, Philipp; De Steur, Laura; Descamps, Sebastien; Divine, Dmitry; Elvevold, Synnøve; Forwick, Matthias; Fransson, Agneta; Fraser, Alexander; Gerland, Sebastian; Granskog, Mats; et al. (Polar Biology, 2022)
Despite the exclusion of the Southern Ocean from assessments of progress towards achieving the Convention on Biological Diversity (CBD) Strategic Plan, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has taken on the mantle of progressing efforts to achieve it. Within the CBD, Aichi Target 11 represents an agreed commitment to protect 10% of the global coastal and marine environment. Adopting an ethos of presenting the best available scientific evidence to support policy makers, CCAMLR has progressed this by designating two Marine Protected Areas in the Southern Ocean, with three others under consideration. The region of Antarctica known as Dronning Maud Land (DML; 20°W to 40°E) and the Atlantic sector of the Southern Ocean that abuts it conveniently spans one region under consideration for spatial protection. To facilitate both an open and transparent process to provide the vest available scientific evidence for policy makers to formulate management options, we review the body of physical, geochemical and biological knowledge of the marine environment of this region. The level of scientific knowledge throughout the seascape abutting DML is polarized, with a clear lack of data in its eastern part which is presumably related to differing levels of research effort dedicated by national Antarctic programmes in the region. The lack of basic data on fundamental aspects of the physical, geological and biological nature of eastern DML make predictions of future trends difficult to impossible, with implications for the provision of management advice including spatial management. Finally, by highlighting key knowledge gaps across the scientific disciplines our review also serves to provide guidance to future research across this important region.
Keywords: Dronning Maud Land; Sørishavet; biofysikk; biogeokjemi; biologi; oseanografi

Three-decade spatial patterns in surface mass balance of the Nivlisen Ice Shelf, central Dronning Maud Land, East Antarctica - Pratap, Bhanu; Dey, Rahul; Matsuoka, Kenichi; Moholdt, Geir; Lindbäck, Katrin; Goel, Vikram; Laluraj, C M; Thamban, Meloth (Journal of Glaciology, 2022)
The coastal Droning Maud Land in East Antarctica is characterized by small ice shelves with numbers of promontories and locally grounded isles, both called ice rises. These ice rises are typically dome-shaped and surface elevations are hundreds of meters above the surrounding ice shelves, which cause strong orographic effects on surface mass balance (SMB). We conducted shallow ice-penetrating radar sounding to visualize firn stratigraphy in the top 35 m over ~400 km of profiles across the Nivlisen Ice Shelf, and in a grid pattern over two adjacent ice rises (Djupranen and Leningradkollen). We tracked six reflectors (isochrones) and dated them using two ice cores taken at the ice rise summits, from which SMB over six periods in the past three decades was retrieved. The overall SMB pattern across the ice shelf remained similar for all periods; however, the eastwest contrast in SMB varies by a factor of 1.5–2 between the Leningradkollen and Djupranen grounding lines. The SMB patterns over the ice rises are more varied owing to complex interactions between topography, snowfall and wind. We use our results to evaluate the regional climate model RACMO2.3p2 in terms of the spatial SMB distribution and temporal changes over the ice shelf and ice rises at regional scale.
Keywords: Dronning Maud Land; glasiologi; isshelf; stratigrafi

Geologisk feltarbeid i Antarktis - Sunde, Øyvind; Elvevold, Synnøve; Engvik, Ane K.; Tholfsen, Audun (Geonytt : et medlemsblad for Norsk geologisk forening, 2022)
Dronning Maud Land, som er Norges territoriale krav i Antarktis, utgjør nærmere 1/6 av det antarktiske kontinentet. Geologisk kartlegging og forskning i Dronning Maud Land er en nasjonal oppgave og i Antarktis-sammenheng kan det betraktes som en måte å vise fortsatt interesse i Norges territoriale krav.
Keywords: Dronning Maud Land; geologi